The Economic-Financial Analysis for Obtaining Repayable Funds at the Territorial Administrative Units - Silvia Bunea (Acta Universitatis Danubius: Oeconomica, 2019)
In our approach through this article we have proposed to solve some problems in relation to public budgets. We live in a world where resources are limited and authorities are looking for ways to help meet the needs of the population. Although the taxes collected from the population are the basic source of financing the public activities and services, they are not always sufficient to achieve all the proposed objectives. Therefore, the authorities need to find new sources of revenue in order to ensure the operating expenses of all public services and at the same time to achieve the proposed investment objectives. In order to obtain additional resources the territorial administrative units can obtain reimbursable funds necessary for achieving the investment objectives and the urban development as well as finding ways to make possible the execution of the budget in such a way that the economic and social life of the administrative units can be improved. The result of our approach consisted in identifying possibilities for improving the execution of budget revenues and expenditures, at the same time, allowed us to develop some conclusions about the reimbursable funds contracted by the Territorial Administrative Unit of the Galati Municipality.